Comparative assessment of post-extension sperm motility in Aseel, Kadaknath and native chicken of Kerala using various semen diluents - Dharaniyedath, Akshay; Sreekumar, Harikrishnan; Harshan, Hiron M; Pallikkattil, Anitha; Gopi, Vineetha Puthanmadathil (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study aimed to compare the preservability of poultry semen using four extenders, viz., Normal Saline (NS), Phosphate Buffered Saline (PBS), Lake Poultry Semen Extender (LPSE), and Beltsville Poultry Semen Extender (BPSE) across three indigenous chicken breeds (Aseel, Kadaknath, and native chicken of Kerala) at both room and refrigeration temperatures. After 8 h at room temperature, Aseel and Kadaknath semen diluted with LPSE demonstrated significantly better progressive sperm motility. For the native chicken of Kerala, both LPSE and BPSE showed promising results. In contrast, the preservability of PBS and NS was notably lower (p<0.01) compared to LPSE and BPSE across all breeds at room temperature. At refrigeration, LPSE outperformed other extenders in retaining progressive sperm motility with BPSE following closely. Notably, after 48 h all samples diluted with NS exhibited zero motility, while the spermatozoa of native chicken of Kerala extended in PBS showed feeble motility. Overall, LPSE emerged as the superior extender for maintaining sperm motility at both temperatures, with BPSE also performing well. Additionally, refrigeration significantly enhanced sperm viability, increasing it up to six fold compared to room temperature storage.